Intranasal Delivery Of Andrographolide Nanoparticles For Improvement Of Cognitive Function: In Vitro And In Vivo Evaluation - Raman, Subashini (2024)
This study explores the neuroprotective potential of andrographolide (ADG), a bioactive compound derived from Andrographis paniculata, and its formulations in various in vitro and in vivo models of neurodegenerative diseases. The present study focuses on the development of a reverse-phase (RP) HPLC method for the quantification of andrographolide (ADG) and neoandrographolide (NEO) in A. paniculata (AP) extract. Through meticulous experimentation, a mobile phase comprising acetonitrile and water (30:70 v/v) was identified as optimal, resulting in sharp peaks and excellent separation of ADG and NEO. The method exhibited good specificity, linearity (r² = 0.999), accuracy (% R.E ≤ 2%), and precision (% RSD ≤ 2%) over a concentration range of 1.0 – 200 μg/ml, complying with US FDA guidelines. Upon development of quantification method, ADG were formulated using single emulsion solvent evaporation method (ADGPNPs and APENPs) and spray drying techniques (NSD NPs, NSD NCs and MSD MNCs). Both the formulation strategies comprising of total 5 formulations were further characterised using SEM, TEM, FTIR, DSC, TGA and XRD. ADGPNPs, APENPs and NSD NPs which were also known to be highly amorphous, have shown a spherical shape with uniform nanoparticles size distribution. Meanwhile, NSD NCs and MSD MNCs which revealed a crystalline nature has a non-uniform size and shape of squares, semi-squares, and rectangle crystals.